The ghosts of Africa : a novel - Stevenson, William, 1924-2013. (New York : Harcourt Brace Jovanovich, 1980)
A fictional account of the adventures of Paul von Lettow, the World War I Prussian commander who created the first modern guerilla army, follows von Lettow and his soldiers as they successfully battle the British
Keywords: History -- War -- Action